2008
DOI: 10.1080/10934520802507621
|View full text |Cite
|
Sign up to set email alerts
|

An application of artificial neural network models to estimate air temperature data in areas with sparse network of meteorological stations

Abstract: In this work artificial neural network (ANN) models are developed to estimate meteorological data values in areas with sparse meteorological stations. A more traditional interpolation model (multiple regression model, MLR) is also used to compare model results and performance. The application site is a canyon in a National Forest located in southern Greece. Four meteorological stations were established in the canyon; the models were then applied to estimate air temperature values as a function of the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Chronopoulos et al (2008) In addition, it is mentioned that the ability of ANN models to take into account any non-linear relationships among meteorological parameters, may provide advantages over traditional methods.…”
Section: Temperaturementioning
confidence: 99%
“…Chronopoulos et al (2008) In addition, it is mentioned that the ability of ANN models to take into account any non-linear relationships among meteorological parameters, may provide advantages over traditional methods.…”
Section: Temperaturementioning
confidence: 99%
“…levels taking into account the measurement time. Recent studies showed that MLP models can be effectively used to evaluate microclimatic conditions in remote mountainous canyons (Chronopoulos et al, 2008;2010).…”
Section: Data Analysis and Artificial Neural Network (Ann) Model Descmentioning
confidence: 99%
“…A robust computational technique, the artificial neural network (ANN) approach, has been applied in many cases due to the advantages of iteration and learning ability, compared to simple regression techniques (Shank et al, 2008). It has been reported that the application of ANN models resulted in satisfactory estimations of air temperature in comparison with multiple linear regression approaches (Chronopoulos et al, 2008;Ustaoglou et al, 2008). Also, these models have been applied successfully to estimate the thermal comfort conditions in mountainous forested areas (Kamoutsis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently ANN models have started to be applied in various aspects of the atmospheric sciences, (Benvenuto et al, 2000;Melas et al, 2000;Mihalakakou et al, 2004;Perez and Reyes, 2006;Tsiros et al, 2009). ANN model applications to meteorological data values estimations are, in general, very few (Cheng et al, 2002;Dimopoulos et al, 2005;Chronopoulos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%